The Effect of Remittance on Economic Growth in Cambodia - Tangtipongkul, Kaewkwan; Khiev, Virak (Journal of Population and Social Studies [JPSS], 2019)
It is estimated that 1.7 million Cambodian migrant workers, accounting for 11% of its population, have sent remittances worth hundreds of millions of USD to their family members in the kingdom in 2018. This great outflow of workers and inflow of remittances has raised the government’s concern about a proper migration policy for harnessing labor migration and remittances to enhance economic development. Therefore, the main objectives of this study are to provide a brief overview of migration policy in Cambodia and to investigate the effect of remittances on economic growth in Cambodia. We estimated multiple regression models, using Ordinary Least Square (OLS) method based on data from the World Development Indicators (WDI) covering the time period from 1993 to 2016. The results of our multiple regression analysis indicate that remittances have had a significant positive impact on the country’s economy, having contributed 0.1180% to its economic growth, thanks to the increased use of remittances in enterprises, agriculture and healthcare in recent years, and financial institutions which have used remittances productively. Based on our findings, we suggest that the government should provide more financial literacy programs to migrant workers and their family members, so that the productive use of remittances in enterprises can be further strengthened.